Cataract Surgical Rate between 2006 and 2010 in Tehran Province - Hassan HASHEMI (Iranian Journal of Public Health, 2015)
Background: Considering population aging in Iran and the importance of cataract surgery in the old age, this study was performed to show the cataract surgical rate (CSR) between 2006 and 2010 in Tehran Province.